2019
DOI: 10.3390/gels5010004
|View full text |Cite
|
Sign up to set email alerts
|

Physical Interactions Strengthen Chemical Gelatin Methacryloyl Gels

Abstract: Chemically cross-linkable gelatin methacryloyl (GM) derivatives are getting increasing attention regarding biomedical applications. Thus, thorough investigations are needed to achieve full understanding and control of the physico-chemical behavior of these promising biomaterials. We previously introduced gelatin methacryloyl acetyl (GMA) derivatives, which can be used to control physical network formation (solution viscosity, sol-gel transition) independently from chemical cross-linking by variation of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 26 publications
(68 reference statements)
5
32
0
Order By: Relevance
“…The reason for the decline in G′ of GM5A5 compared to GM5 hydrogels was interpreted before by a reduction of physical interactions between gelatin derivative macromolecules due to the higher total degree of modification, as was also observed for GM hydrogels which were cured above the gelation point, like in this study . GM5 hydrogels assumingly contain a relevant concentration of relatively strong physical cross‐links in addition to chemical cross‐links, making the hydrogel stiffer than GM5A5 hydrogels and similarly stiff like GM10 hydrogels.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The reason for the decline in G′ of GM5A5 compared to GM5 hydrogels was interpreted before by a reduction of physical interactions between gelatin derivative macromolecules due to the higher total degree of modification, as was also observed for GM hydrogels which were cured above the gelation point, like in this study . GM5 hydrogels assumingly contain a relevant concentration of relatively strong physical cross‐links in addition to chemical cross‐links, making the hydrogel stiffer than GM5A5 hydrogels and similarly stiff like GM10 hydrogels.…”
Section: Resultssupporting
confidence: 71%
“…However, it has to be recognized that the DM not only has an impact on the cross‐link density of resulting hydrogels. Upon methacryloylation, many other relevant physico‐chemical properties are changed too, such as hydrophilicity, isoelectric point (IEP), or the ability to form physical hydrogels . For example, previous data suggested that, in fact, the hydrophilicity of GM‐based materials had an impact on releases of vascular endothelial growth factor .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated in how far the formation of both, physical and chemical cross-links, in GM hydrogels can act synergistically to improve mechanical properties. To this end, a sequential cross-linking procedure of GM hydrogels was applied by several authors, which increased the maximum strength 6 , compressive modulus 7 , 8 , storage modulus 9 , 10 and E-modulus distinctly 11 . During this sequential cross-linking procedure, the hydrogel precursor solutions were held at rather low temperatures, e.g .…”
Section: Introductionmentioning
confidence: 99%
“…It can also be used to tune the properties of the crosslinked gels by reducing the number of crosslinks at preserved biopolymer concentration: GMA is covalently integrated into the biopolymer network due to the presence of methacrylic groups. However, masking of amino-and hydroxy groups by acetylation results in less effective crosslinking due to sterical hindrance and impeded physical interactions 44 .…”
Section: Modification Of Gm-hydrogels With Gelatin and Acetylated Gm mentioning
confidence: 99%
“…However, it has to be noted that lower degrees of modification lead to stronger physical gel formation if the processing temperature is below the gelation temperature. This is associated with helix-formation of G and GM molecules, more effective crosslinking and thus stiffer gels 44 . Consequently, the synthesis and handling of tailored GM derivatives requires much experience.…”
Section: Modification Of Gm-hydrogels With Gelatin and Acetylated Gm mentioning
confidence: 99%